2006
DOI: 10.1152/ajpgi.00357.2005
|View full text |Cite
|
Sign up to set email alerts
|

cGMP modulation of ACh-stimulated exocytosis in guinea pig antral mucous cells

Abstract: In guinea pig antral mucous cells, ACh stimulates the Ca2+-regulated exocytosis, which has a characteristics feature: an initial transient phase followed by a sustained phase. The effects of cGMP on ACh-stimulated exocytosis were studied in guinea pig antral mucous cells using video microscopy. cGMP enhanced the frequency of ACh-stimulated exocytotic events, whereas cGMP alone did not induce any exocytotic events under the ACh-unstimulated condition. cGMP did not stimulate either Ca2+ mobilization or cAMP accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 34 publications
4
41
0
Order By: Relevance
“…The previous study demonstrated that 8-BrcGMP enhances the initial phase of Ca 2ϩ -regulated exocytosis in antral mucous cells (14). In this study, we confirmed the same effects of 8-BrcGMP on the frequency of ACh-stimulated exocytotic events.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The previous study demonstrated that 8-BrcGMP enhances the initial phase of Ca 2ϩ -regulated exocytosis in antral mucous cells (14). In this study, we confirmed the same effects of 8-BrcGMP on the frequency of ACh-stimulated exocytotic events.…”
Section: Resultssupporting
confidence: 89%
“…An accumulation of cAMP, which accelerates the priming step and the fusion step, also significantly increases the frequency of the initial phase in Ca 2ϩ -regulated exocytotic events. However, cGMP accelerates the priming step of Ca 2ϩ -regulated exocytosis, leading to an increase in the frequency of the initial phase; the cGMP-induced enhancement of the initial phase was not affected by protein kinase A (PKA) inhibitors (PKI-amide and H-89) (14).…”
mentioning
confidence: 99%
“…In antral mucous cells, the Ca 2+ -regulated exocytosis which is activated by ACh (acetylcholine) is the main mechanism for mucin release (8,14,15,19) and is modulated by many substances, such as cAMP, NO, cGMP, intracellular Cl − , and arachidonic acid (AA) (8,14,19,(21)(22)(23)(24). NO is synthesized by nitric oxide synthase 1 (NOS1) and enhances the Ca 2+ -regulated exocytosis mediated via cGMP accumulation in antral mucous cells (28).…”
mentioning
confidence: 99%
“…NO is synthesized by nitric oxide synthase 1 (NOS1) and enhances the Ca 2+ -regulated exocytosis mediated via cGMP accumulation in antral mucous cells (28). Previous studies demonstrated that cGMP increases the releasable pool of mucous granules by accelerating the ATP-dependent priming leading to the enhancement of Ca 2+ -regulated exocytosis in antral mucous cells (11,19). Peroxisome proliferation activation receptor α (PPARα), the natural ligands of which are fatty acids including AA, enhances the Ca 2+ -regulated exocytosis in antral mucous cells (21,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation